The Interaction of Organizational Capabilities and Individual Competences for Open Innovation in Small and Medium Organizations - Pranciulytė-Bagdžiūnienė, Ilma; Petraitė, Monika (Information & Media, 2019)
Open innovation serves as a principal paradigm for success in diverse and dynamic business environments, as it gives the promise of a better-marked acceptance, a higher level of novelty, and managed innovation risks. However, SMEs face a critical challenge in developing open innovation capabilities and establishing new organizational processes that would empower employees to perform in open innovation regimes. We analyze the mediating role of organizational capabilities for employing and facilitating individual competences for innovation performance improvement as based on a survey of 266 SMEs. This study aimed to identify links between organizational capabilities and individual comp etences in AI for innovation performance in SMEs. The results of our study showed that organizational capabilities in AI at the level of organizations play a role as a mediator between competences for AI at the individual level and the progress of innovations. Considering that organizational skills in AI (organizational culture openness, organizational learning and trust, knowledge management systems, etc.) are strong organizational tools that help to increase the efficiency of AI and individual competences (to enhance employee creativity, enhance interaction with partners) as well as management competences (flexibility, ability to work with various professional communities, strategic thinking, etc.). This study partially refutes the assumptions that SMEs can only achieve innovative progress through individual competences in AI. Organizational capabilities in AI are also very important for AI implementation.
Keywords: organizational capabilities; individual competences; open innovation; small and medium organizations